Realization of Low Cross-Polarization Level for GF-3 SAR Antenna - Jian Mi; Hongbing Sun; Guodong Song; Ying Xing; Xuhao Zhao (International Journal of Antennas and Propagation)
In the polarimetric synthetic aperture radar (PolSAR) system, crosstalk error is the key parameter for polarimetric imaging. The source of crosstalk is mostly from the cross-polarization level of the SAR antenna subsystem. To meet the requirements of PolSAR observing modes, a low cross-polarization level under −35 dB is realized for the SAR antenna of the GF-3 satellite. In this paper, we will describe the principles and methods for implementation of low cross-polarization level. The two polarized RF chains are totally independent to ensure high isolation, and a dual-polarized waveguide slot antenna subarray is designed with a low cross-polarization level. Besides, the low taper efficiency of the cross-polarization pattern contributes to reduce the cross-polarization, showing the advantage of the phased array antenna in the PolSAR system. The paper also displays the measured results of cross-polarization for the GF-3 SAR antenna. The study gains a better understanding of the cross-polarization pattern for phased array antenna. The methods utilized here can be extended to other polarimetric SAR systems.